107k views
2 votes
Help please 1. Describe the transformations necessary to transform the graph of

f(x) to that of g(x)
f(x) = x² and g(x) = 3(x - 1)² + 4

User Toji
by
5.5k points

1 Answer

2 votes

Here are all the steps, and what they do:

STEP 1: HORIZONTAL TRANSLATION

We transform


x^2\mapsto (x-1)^2

The general transformation is


f(x)\mapsto f(x+k)

These transformations translate the graph horizontally, k units to the left if k>0, k units to the right if k<0.

In this case, k = -1, so we translate the original graph 1 unit to the right.

STEP 2: VERTICAL STRETCH

We transform


(x-1)^2\mapsto 3(x-1)^2

The general transformation is


f(x)\mapsto kf(x)

These transformations stretch the graph vertically. The graph expands if |k|>1, while it shrinks if 0<|k|<1. If k is negative, we also reflect the graph with respect to the x axis.

In this case, k = 3, so we stretch the graph vertically by a factor 3.

STEP 3: VERTICAL TRANSLATION

We transform


3(x-1)^2\mapsto 3(x-1)^2+4

The general transformation is


f(x)\mapsto f(x)+k

These transformations translate the graph vertically, k units up if k>0, k units down if k<0.

In this case, k = 4, so we translate the graph 4 units up.

So, we start from the original graph of
f(x)=x^2 and we:

  • Translate it 1 unit to the right
  • Stretch it vertically by a factor 3
  • Translate it 4 units up

(the order is important!)

to get the graph of
g(x)=3(x-1)^2+4

User Christian Vielma
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.